TANGGUNG JAWAB BISNIS LAYANAN OJEK ONLINE BAGI PENUMPANG YANG MENGALAMI KECELAKAAN BERDASARKAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN DI KOTA BENGKULU - itok dwi kurniawan (Jurnal Hukum Lex Generalis, 2024)
This paper discusses the responsibility of online motorcycle taxi services in Bengkulu City in the event of an accident involving passengers. This study uses a type of empirical legal research, which examines the gap between applicable legal provisions and practice in the field. Based on Article 63 Paragraph (1) of the Regulation of the Minister of Transportation No. PM 108/2017, transportation services can use information technology to facilitate bookings. Findings in the field show that business actors only provide compensation if they meet certain conditions, while full responsibility for accidents lies with the driver. In the employment agreement, it is explained that the risk of negligence, including delay, accident, or loss of goods, is the responsibility of the driver.